CORPORATE GOVERNANCE AND FRAUDULENT FINANCIAL REPORTING AMONG MALAYSIAN PUBLIC LISTED COMPANIES - Moganasundri Devarajar; Muhammad Shabir Shaharudin; Anwar Allah Pitchay; Hasnah Haron; Yuvaraj Ganesan, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Financial reporting is essential for the publicly listed companies as most of the company's stakeholder depended on the financial statement to make a business decision. Although many initiatives have implemented by relevant authorities to enhance financial reporting standards to overcome the fraudulent financial reporting (FFR). However, the issues still happening, for example, cases such as 1MBD, Lembaga Tabung Haji (LTH), Wirecard AG and British Home Stores (BHS). The paper aimed to investigate the impact of corporate governance (CG) attributes, namely audit committee size, board independence, multiple directorships, board size and non-audit services on FFR. This study is categorised as a crosssectional analysis, using a quantitative approach to gain an overview of fraudulent financial reporting. A total of 260 listed companies selected from Bursa Malaysia and the data was analysis used PLS-SEM. The findings revealed that the multiple directorships and non-audit service impact significantly related to FFR. This study made practical implications by helping the regulators, and accounting experts develop principles that help companies comply with financial reporting regulation. Accurately report the financials statement enhances stakeholder's knowledge in the decision-making process.